Nitrate supplementation for sports performance - Ali, A. (Elite Training Seminar Series, 2016)
Dietary nitrate supplementation (consumed as beet-root juice) has been shown to have performance and health-related benefits in athletes and patients, re-spectively. This presentation will provide the theoreti-cal underpinnings for nitrate supplementation, its role in increasing nitric oxide - a physiological signalling molecule that has been shown to affect a wide range of physiological processes - as well as the available performance-related information for endurance, strength and power athletes.